Surau di Dunia Maya (Reinkarnasi Tambo Minangkabau di Era Konvergensi Media) - Sheiful Yazan (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2019)
Tambo is often connoted as "the treasure of the past" which has been lost in the Minangkabau community. In the past, Tambo Minangkabau was studied in surau as a place to inherit traditional values. Now, surau adat has almost disappeared in the midst of society. But, in the current era of Convergent Media, the attention and study of Tambo Minangkabau is growing and developing in various forms. This article discusses the emergence and revival of discussions and studies of Minangkabau Tambo in various Convergent Media as new "suraus" in cyberspace.